2015
DOI: 10.1016/j.cca.2014.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of 14-3-3 proteins, serotonin, gamma enolase and pyruvate kinase identified in clinical samples from patients diagnosed with colorectal cancer

Abstract: The diagnosis and management of CRC could be enhanced by the discovery and validation of new candidate biomarkers, as found in this study, aimed at facilitating early detection and/or patient stratification together with providing information on the complex behaviour of cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 68 publications
0
18
0
Order By: Relevance
“…As metabolomics studies often identified a wide range of metabolites due to the variety of analytical platforms, clinical protocols, and sample handling procedures used, leveraging an independent population for replication using the same platform and similar protocols is essential to ensure robustness of findings. To date, only few studies have used a discovery‐replication design to reproduce results in independent study populations . Two of these studies investigated metabolic differences between colorectal cancer patients and apparently healthy individuals; a third study evaluated metabolomic differences between matched tumor and healthy colon tissue samples from colorectal cancer patients .…”
Section: Introductionmentioning
confidence: 99%
“…As metabolomics studies often identified a wide range of metabolites due to the variety of analytical platforms, clinical protocols, and sample handling procedures used, leveraging an independent population for replication using the same platform and similar protocols is essential to ensure robustness of findings. To date, only few studies have used a discovery‐replication design to reproduce results in independent study populations . Two of these studies investigated metabolic differences between colorectal cancer patients and apparently healthy individuals; a third study evaluated metabolomic differences between matched tumor and healthy colon tissue samples from colorectal cancer patients .…”
Section: Introductionmentioning
confidence: 99%
“…The optimized methodology has been previously described in detail (17). Peptide mixtures (5-µl volume) were loaded onto a C18 trap column [Acclaim™ PepMap™ 100 C18 LC column; 300 mm internal diameter (id) × 5 mm, 5 mm particle size, 100 Å pore size; Dionex Corporation; Thermo Fisher Scientific, Inc.).…”
Section: Methodsmentioning
confidence: 99%
“…Data alignment was based on the LC retention time of each sample (17). A reference sample was established, the retention times of all other replicates were aligned to this reference and peak intensities were then normalised.…”
Section: Methodsmentioning
confidence: 99%
“…Such different behavior is much likely due to the ability of serotonin to act in a concentration-dependent manner, as well as in its capability to activate distinct signaling pathways, depending on the receptor subtype present at various tumor stages. Coherently, high serotonin levels, correlating with the tumor stage, distant metastases and a poor prognosis, have been found in the serum of patients with different solid tumors [131,[135][136][137], whereas low concentrations have been found in hepatocellular carcinoma patients, who showed recurrence after partial hepatectomy [118]; in untreated breast adenocarcinoma or malignant melanoma patients, where the phenotype (also associated with a high ATP/ADP ratio and index of delta storage pool deficiency) was more marked in regionally spread malignant tumors [138].…”
Section: Platelet-derived Bioactive Compoundsmentioning
confidence: 99%